BENTUK TINDAK TUTUR ILOKUSI ASERTIF PADA KONTEN PODCAST TEMATIK PRODUKSI LPP RRI PURWOKERTO - Muhamad Razief Riski Abadi; Melasarianti, Lalita; M. Riyanton (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of assertive illocutionary acts found in the podcast titled “Nguri-uri Budaya melalui Seni Tari” produced by LPP RRI Purwokerto. The podcast was selected as the data source because it presents spontaneous spoken interactions that reflect cultural communication practices in digital media. A qualitative approach with a descriptive method was applied to portray language use within its context without manipulating the communication process. The research data consist of spoken utterances from the host and guest speakers, which were fully transcribed and then selected based on their relevance to the category of assertive illocutionary acts. Data collection was conducted using the Simak Bebas Libat Cakap (SBLC) method and the note-taking technique, while data analysis employed the padan method by considering speaker relations, the speech situation, and communicative goals emerging in the dialogue. To clarify the function of each utterance, the Pilah Unsur Penentu (PUP) technique was used during data classification. The findings show that assertive illocutionary acts in this podcast appear in several forms, namely informing, explaining, reporting, stating, affirming, acknowledging, and expressing pride. These utterances are used by speakers to convey factual information, personal experiences, and perspectives regarding Banyumasan traditional dance and its surrounding dynamics. The dominance of assertive forms illustrates the podcast’s role as an informative communication medium that emphasizes clarity and credibility in delivering messages to the audience. The results further indicate that the podcast serves not only as entertainment but also as a space for disseminating cultural knowledge that is widely accessible. Moreover, this study reinforces that podcasts are relevant data sources in pragmatik research because they provide spoken interactions rich in variations of speech acts.